Adapting Form-Focused and Meaning-Focused Instruction in the Digital Post-Pandemic English Classroom - Pringgadani, Ridha Muhibbin Amil; Anjaniputra, Agung Ginanjar (Institut Agama Islam Negeri Parepare, 2025)
Form-Focused Instruction (FFI) and Meaning-Focused Instruction (MFI) have been known in the field of English Language Teaching. However, since the COVID-19 pandemic disrupted education, the learning situations in a classroom can no longer rely on traditional ways. Following the shifts, this study aims to investigate the implementation of FFI and MFI in an English language classroom at a senior high school in Indonesia. This study uses a qualitative case study approach, and the data was collected through semi-structured interviews and then analyzed using thematic analysis based on the characteristics identified by Ellis (2001) and Pawlak (2006). The findings reveal an integrated implementation of FFI and MFI. The use of explicit grammar instruction, corrective feedback, and structured learning based on Kurikulum Merdeka reflects the implementation of FFI. On the other hand, the implementation of MFI is reflected in collaborative and learner-centered activities, real-world examples, and a genre-based approach (GBA). Additionally, due to the pandemic shift, the use of digital tools also facilitated learning beyond traditional situations. The findings also show the adaptability of FFI and MFI in the digital era since the reliance on digital tools has increased post-pandemic situations. The teachers are suggested to adapt to the digitalized era by equipping them with digital literacy. However, the study's scope is limited to a single school, and the context identified is only after the COVID-19 pandemic.